Is the sexual performance of obese women different? A narrative review study - Maryam Amighi; zohreh keshavarz; Mahdi Alam-Rajabi; Maliheh Nasiri (Mashhad University of Medical Sciences, 2023)
Introduction: Considering the increasing prevalence of obesity and the importance of examining the relationship between sexual dysfunction and obesity in women and the need for systematic reviews that summarize the results of similar studies, the present study was systematically conducted with aim to determine sexual performance in women with obesity using the questionnaire of the female sexual function index (FSFI).  Methods: In this systematic review, based on the PRISMA checklist, a literature review was conducted with a systematic approach in the field of examining sexual function in obese women using the FSFI questionnaire. In this regard, a systematic review was conducted in Web of Science, PubMed, MEDLINE, etc. databases. The keywords that were selected included sexual function, obesity, and women. In this systematic review, all English and Persian observational articles from the inception to 2022 were used. Results: In this study, 761 articles were initially extracted from the investigated databases and sources, and finally, five published articles met the criteria for entering this systematic review. Among the articles, four articles were in English and 1 article was in Persian. In these studies, the sexual performance scores obtained from the obese group were evaluated as a total score, sexual desire, sexual arousal, vaginal moisture, orgasm, sexual satisfaction, and pain. As this review was conducted with the aim of determining sexual function in obese women using the FSFI questionnaire, in most studies, a decrease in scores of the questionnaire and in different areas of sexual function was observed. Conclusion: According to the results of most studies examined in this systematic review, sexual dysfunctional in obese women is high. Therefore, it is recommended to evaluate the sexual function in obese people in order to identify and treat people who need intervention.